Multisystem inflammatory syndrome (MIS): a multicentre retrospective review of adults and adolescents in South Africa. (October 2021) - van Heerden, Jennifer; Nel, Jeremy; Moodley, Pramodhini; Govender, Preesha; Hooijer, Jonathan; Ickinger, Claudia; Lahri, Sa'ad; Louw, Elizabeth; Rabie, Helena; Reddy, Denasha; Tsitsi, Jacob; Venter, Michelle; et al.
Highlights: This is the largest multicentre review of adults and adolescents with multisystem inflammatory syndrome (MIS) in Africa. Despite heterogeneous presentations, a pattern of disease is discernible. Haemodynamic instability was prominent, requiring acute intensive care. Increased awareness of MIS in adults and adolescents in low- and middle-income countries is important. Abstract: Objectives: The aim of this study was to add to the descriptive data pertaining to the epidemiology, presentation, and clinical course of multisystem inflammatory syndrome (MIS) temporally associated with coronavirus disease 2019 in adults and adolescents from low- and middle-income countries. Methods: Patients presenting to the adult wards (14 years and older) of three academic hospitals in South Africa, who were diagnosed with MIS between August 1, 2020 and May 31, 2021, were reviewed retrospectively. The presentation, laboratory and radiographic findings, and clinical course are described. Results: Eleven cases of MIS were reported, four in adolescents (14–19 years) and seven in adults (≥19 years). Fever was universal. Gastrointestinal symptoms (90.9%), cardiorespiratory abnormalities (90.9%), and mucocutaneous findings (72.7%) were prominent. Echocardiography in 10/11 patients (90.9%) showed a median left ventricular ejection fraction of 26.3% (interquartile range 21.9–33.6%). All patients required high care admission and 72.7% required inotropic support. Glucocorticoids were initiated in all cases and 72.7% received intravenous immunoglobulin. Conclusions: This constitutes the largest multicentre review of adults and adolescents with MIS in Africa. MIS may be overlooked in resource-limited settings, and heightened suspicion is needed in patients with multi-organ dysfunction, especially where repeated investigations for other aetiologies are negative. Graphical abstract: Image, graphical abstract